Ketangkasan Kepemimpinan dalam Manajemen Krisis: Pembelajaran dari Pemimpin Pendidikan Selama Masa Transisi Pasca-Pandemi - Masrur Luai Sadullah (Visionaria: Journal of Educational Innovation Management, 2025)
The COVID-19 pandemic has significantly disrupted the global education system, demanding agile and adaptive leadership from school leaders to navigate crises marked by uncertainty, complexity, and volatility. This study aims to analyze how agile leadership was practiced in educational contexts during the post-pandemic transition and how these practices intersect with contemporary leadership theories. Employing a library research approach, the study systematically reviewed scholarly articles, policy reports, and academic books published between 2018 and 2024 that discuss crisis management, distributed leadership, and leadership resilience in education. The findings reveal that agile leadership is manifested not only through rapid and flexible decision-making, but also in empathetic communication, collaborative governance, and distributed leadership practices. These elements enhance organizational resilience and collective wellbeing in schools. The study further develops a conceptual framework that integrates agile, adaptive, and distributed leadership as a relevant model for VUCA environments. The novelty lies in positioning agile leadership as a sustainable leadership approach that bridges theory and practice. This research contributes theoretically by expanding the discourse on agile leadership into education and practically by recommending agility-based training programs to prepare school leaders for future crises.